Divergence of NHS choice policy in the UK: what difference has patient choice policy in England made?. (October 2013) - Sanderson, Marie; Allen, Pauline; Peckham, Stephen; Hughes, David; Brown, Menna; Kelly, Grace; Baldie, Debbie; Mays, Nicholas; Linyard, Alison; Duguid, Anne
Objectives: To examine the types of choices available to patients in the English NHS when being referred for acute hospital care in the light of the divergence of patient choice policy in the four countries of the UK. Methods: Case studies of eight local health economies in England, Scotland, Northern Ireland and Wales (two in each country); 125 semi-structured interviews with staff in acute services providers, purchasers and general practitioners (GPs). Results: GPs and providers in England both had a clear understanding of the choice of provider policy and the right of patients to choose a provider. Other referral choices potentially available to patients in all four countries were date and time of appointment, site and specialist. In practice, the availability of these choices differed between and within countries and was shaped by factors beyond choice policy, such as the number of providers in an area. There were similarities between the four countries in the way choices were offered to patients, namely lack of clarity about the options available, limited discussion of choices between referrers and patients, and tension between offering choice and managing waiting lists. Conclusions: There are challenges in implementing pro-choice policy in health care systems where it has not traditionally existed. Differences between England and the other countries of the UK were limited in the way choice was offered to patients. A cultural shift is needed to ensure that patients are fully informed by GPs of the choices available to them.